Application of Multiprocessing Technology of Motion Video Image Based on Sensor Technology in Track and Field Sports. (11th February 2022) - Xu, Shaofeng; Chen, Junmeng
Abstract : To improve the accuracy of track and field sports feature recognition, this paper combines sensor technology to improve the motion video image multiprocessing technology and gives the basic principles of image registration. Moreover, this paper chooses a model based on projection transformation. When using a high-speed linear CCD, only the image information on the finish line is collected. Unlike the previous high-speed area CCD cameras that can capture runway information, linear CCDs are used to collect only the image information on the finish line, and the data is collected and processed through sensor technology. The research shows that the application effect of the motion video image multiprocessing technology based on sensor technology in track and field sports proposed in this paper has good practical effects.